Influencia del Juego ‘’Dominó Ortográfico’’ en el mejoramiento de la ortografía de las niñas de cuarto grado de Educacion Primaria de la Institución Educativa N°81007 ‘’Modelo’’ de Trujillo, 2016 - Santillán Valle, Marjhory Solange (2018)
The present research aimed at the application of the orthographic domino to improve spelling in 4th grade girls from the I. E. No. 81007 Model, from the city of Trujillo in 2016. For this study, a sample of 25 students with similar characteristics was selected. The type of research is Applied, the design of the research is Quasi Experimental with Pre and Post Test, the results of the Pre Test show that before the application of the spelling domino to improve spelling, girls showed little significant spelling performance. After applying the spelling domino for improvement in spelling and according to the Post Test, the children show a significant increase in their spelling.